Discursul absolut al teologiei - Turcan, Nicolae (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
This article first defines the absolute discourse, then discusses its possibility in theology, as well as the relationships between language, thought, and reality as they derive from the spirituality and life of the Eastern Church. Theology must face several problems—including the paradox of transcendence, the violence of metaphysics, onto-theology, and the duplicity of language itself—, but the Revelation of the Absolute itself legitimizes the theological discourse. By using both affirmations and negations, theology reveals an iconic structure of discourse that opens itself towards life and spirituality. The conclusion is that, in the absolute discourse of theology, words, even ineffable ones, are insufficient without life.